2010
DOI: 10.1038/cmi.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A in combination with TNF-α selectively induces Th2 cell-promoting dendritic cells in vitro with an estrogen-like activity

Abstract: Bisphenol A (BPA) is a monomer used in manufacturing a wide range of chemical products, including epoxy resins and polycarbonate. BPA, an important endocrine disrupting chemical that exerts estrogen-like activities, is detectable at nanomolar levels in human serum worldwide. The pregnancy associated doses of 17b-estradiol (E2) plus tumor-necrosis factor-a (TNF-a) induce distorted maturation of human dendritic cells (DCs) that result in an increased capacity to induce T helper (Th) 2 responses. The current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…Using murine as well as human DC differentiation cultures we could also observe diminished IL-12 levels in the presence of BPA. This was similar to findings by Guo et al ., who demonstrated that BPA-exposed DC produced higher levels of IL-10 relative to that of IL-12 and preferentially induced Th2 deviation [16]. However, based on this assumption exposure of the adult mice during antigen sensitization should also enhance the allergic immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using murine as well as human DC differentiation cultures we could also observe diminished IL-12 levels in the presence of BPA. This was similar to findings by Guo et al ., who demonstrated that BPA-exposed DC produced higher levels of IL-10 relative to that of IL-12 and preferentially induced Th2 deviation [16]. However, based on this assumption exposure of the adult mice during antigen sensitization should also enhance the allergic immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The studies mainly describe an interference with hormone receptors like the estrogen receptor. However, these data are also inconsistent and show contrasting results [16], [17]. The inconsistency in the findings might arise due to different observation periods in human studies and the diverging design of the animal models, including the use of varying BPA doses and the route of exposure [18].…”
Section: Introductionmentioning
confidence: 99%
“…Integrating the totality of the data is challenging, but when one attempts to do so, the picture that forms is one in which exposure to BPA at or below 50 μg/kg/d generally has little effect on adaptive immune responses, but consistently modulates some aspects of inflammation. Altered responses of cells from BPA treated animals, such as elevated T-helper (T H )-2 cell cytokine production, enhanced ex vivo lymphocyte proliferation have been reported (Gallo et al, 2008; Guo et al, 2010); however, when these endpoints were examined in studies that used multiple doses of BPA, exposures in the mg/kg/d range generally altered these endpoints, whereas doses in the μg/kg/d range were rarely shown to affect metrics of lymphocyte function or alter disease progression (Lee et al, 2003; Sawai et al, 2003; Goto et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, BPA is generally classified as an endocrine-disrupting chemical (EDC), and in recent years there has been much discussion both in the scientific community and in general public regarding the possible adverse health effects of exposure to EDC agents. Third, estrogens and other hormones control many aspects of immune and inflammatory responses (Bebo et al, 2001; Gallo et al, 2008; Guo et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…BPA induced complex effects on the immune response mainly suppressing antigen-specific cytokine production of T cells. Guo et al (2010) have performed in vitro experiments studying the effect of human monocyte-derived dendritic cells (DC) exposed to BPA on the cytokine production and expression of ER-α, ER-β and GPR30 in naïve human Th cells. This study demonstrated that the presence of BPA during DC maturation influences the function of human DCs, thereby polarizing the subsequent Th response.…”
Section: Effects On Signal Transfer and Gene Expressionmentioning
confidence: 99%